Evaluasi Sistem Informasi Administrasi Terhadap Kualitas Pelayanan dan Kinerja Program Studi - Febrianto Sabirin; Dewi Sulistiyarini (Educatio, 2020)
The administrative information system is a website-based information system that is used to assist the administrative activities of the Computer and Information Technology Education Program (P.TIK) of the IKIP PGRI Pontianak. The purpose of this study was to determine the service quality and performance of the P.TIK study program after implementing the study program administration information system. The method used in this research is a survey method with a descriptive evaluative research approach. The research sample consisted of 185 students of P.TIK IKIP PGRI Pontianak using purposive sampling technique by selecting students who had used the study program administration information system. The data collection tool used was a closed questionnaire with data analysis techniques using descriptive statistics. The results showed that the service quality and performance of the study program after using the administrative information system were in the very good category